El proemio de Valerio Flaco. Una lectura retórica - Río Torres-murciano, Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2005)
Historical and even political readings of the proem of the Argonautica have always paid attention to some reference outside the text, whose interpretation becomes then a search after the hidden quid, either the date of the first twenty one lines or the political engagement of the poem. This «rhetorical reading» now proposed is just another way of framing the issue, a way that takes care not of the quid but of the quale, i. e. of the rethorical modality by which the text constitutes itself within its topoi and tropoi. At the end, rhetorical patterns provide us with a usefull tool the to take a glance over the proem as a problematic beginning which pretends to conquer the future by rewriting the past, somehow a trope for the impossibility of leaving temporality.